From Tolerance to Transformation: An Intercultural Approach to Christian Education through Theology and Communication Ethics - Nella Mariana Panjaitan (Indonesian Journal of Christian Education and Theology, 2026)
In many contexts, religious education practices stop at passive tolerance coexisting without meaningful dialogue thus failing to build just relationships in plural societies. This article aims to develop an approach to Christian Religious Education (CRE) that goes beyond transmissional models toward dialogical and transformative learning. This study employs a literature review with thematic and comparative analysis of theological, educational, and social science literature. Conceptual data were synthesized to formulate a learning framework relevant to pluralistic contexts. The findings show that integrating interculturality, theology that affirms human dignity, and ethical communication strengthens reflective and participatory faith formation. The article proposes the Mutual Transformation Framework, a model that places teachers and students in a process of reciprocal transformation through epistemological awareness, intercultural encounters, inclusive theological foundations, and reflective communication. This framework has the potential to deepen faith understanding, foster social sensitivity, and cultivate commitment to justice and peace. The study offers a conceptual contribution to the development of intercultural CRE and recommends further implementation studies in school and church settings.